CFD study of an air–water flow inside helically coiled pipes. (November 2015) - Colombo, Marco; Cammi, Antonio; Guédon, Gaël Raymond; Inzoli, Fabio; Ricotti, Marco Enrico
Abstract: CFD is used to study an air–water mixture flowing inside helically coiled pipes, being at the moment considered for the Steam Generators (SGs) of different nuclear reactor projects of Generation III+ and Generation IV. The two-phase mixture is described through the Eulerian–Eulerian model and the adiabatic flow is simulated through the ANSYS FLUENT code. A twofold objective is pursued. On the one hand, obtaining an accurate estimation of physical quantities such as the frictional pressure drop and the void fraction. In this regard, CFD simulations can provide accurate predictions without being limited to a particular range of system parameters, which often constricts the application of empirical correlations. On the other hand, a better understanding of the role of the centrifugal force field and its effect on the two-phase flow field and the phase distributions is pursued. The effect of the centrifugal force field introduced by the geometry is characterized. Water is pushed by the centrifugal force towards the outer pipe wall, whereas air accumulates in the inner region of the pipe. The maximum of the mixture velocity is therefore shifted towards the inner pipe wall, as the air flows much faster than the water, having a considerably lower density. The flow field, as for the single-phase flow, is characterized by flow recirculation and vortices. Quantitatively, the simulation results are validated against the experimental data of Akagawa et al. (1971) for the void fraction and the frictional pressure drop. The relatively simple model of momentum interfacial transfer allows obtaining a very good agreement for the average void fraction and a satisfactory estimation of the frictional pressure drop and, at the same time, limits the computational cost of the simulations. Effects of changes in the diameter of the dispersed phase are described, as its value strongly affects the degree of interaction between the phases. In addition, a more precise treatment of the near wall region other than wall function results in a better definition of the liquid film at the wall, although an overestimation of the frictional pressure drop is obtained. Highlights: Eulerian multiphase model is applied to air–water flow inside helically coiled pipe. Influence on the flow of centrifugal force introduced by geometry is characterized. Numerical results are validated through comparison with experimental data. Void fraction and frictional pressure drop are predicted with satisfactory accuracy. CFD model is less limited in its range of applicability than available correlations.